Analysis of 'sensitive' periods of fetal and child growth. (2nd April 2018) - Zhang, Xun; Tilling, Kate; Martin, Richard M; Oken, Emily; Naimi, Ashley I; Aris, Izzuddin M; Yang, Seungmi; Kramer, Michael S
Abstract: Background: Birth weight and weight gain in infancy and early childhood are commonly studied as risk factors for later cardiometabolic diseases. In this study, we explore methods for quantifying weight gain during different age periods and for comparing the magnitude of the associations with later blood pressure. Methods: Based on data from a birth cohort study nested within a large cluster-randomized trial with repeated measures of weight from birth to 16 years of age, we compared the results of four analytic approaches to assess sensitive periods of growth in relation to blood pressure at age 16 years. Results: Approaches based on z-scores of weight or weight gain velocity (both standardized for age and sex) or on regression-based conditional weight standardized residuals yielded more coherent results than an approach based on absolute weight gain velocity. Weight gain standardized by sex and age was positively associated with blood pressure at 16 years at all postnatal age periods, but the magnitude of association was larger during adolescence (11.5–16 years) than during earlier intervals (0–3 months, 3–12 months, 1–6.5 years or 6.5–11.5 years). Conclusions: Standardization of weight and weight gain by age and sex, or regression-based standardized residuals based on conditional weight, reflects relative gain and thus accounts for the rapid weight gains normally observed in early infancy and puberty. Adolescence appears to be a more sensitive period for relative weight gain effects on later blood pressure than earlier periods, even those of similar duration.